The Evolution of Central Government Ministries' (CGM) Libraries in India: Bridging Education and the Dynamic Tech World - Mahawariya, Kimi (Qualitative and Quantitative Research Center, 2025)
In an era where the synergy between educational infrastructure and the dynamic technological landscape is redefining knowledge management, the evolutionary adaptability of government libraries becomes the linchpin in bridging the gap between traditional policy support and the digital future. This study investigates the technological evolution of 32 Central Government Ministries’ (CGM) libraries in Delhi from 2010 to 2023, specifically analyzing their transition regarding e-resources, ICT tools, automation, and housekeeping activities. These institutions play a critical role in facilitating policy formulation and legislation while providing access to essential documentation for parliamentarians, bureaucrats, and researchers. Utilizing a mixed-method approach through structured questionnaires administered to library heads, the research quantitatively and qualitatively evaluates modernization efforts. Results indicate a progressive integration of modern ICT tools to align with global standards. Specifically, the Ministry of Power Library holds the largest e-resource collection, while the Central Secretariat Library leads in ICT infrastructure and management software. Significant milestones were achieved in automation; by 2023, 21 libraries were fully automated, 24 had adopted Library Management Software (LMS), and 18 utilized automated modes for housekeeping functions. While network sharing remained consistent, these figures reflect a positive modernization trajectory. This research provides a crucial outlook on the status of CGM libraries, identifying systemic hurdles to guide future developmental plans. Uniquely, this study offers the first comprehensive, fourteen-year longitudinal assessment of Indian government libraries, filling a significant gap in the literature regarding their evolutionary adaptation within the modern technological world.